Laparoscopy in Gynecologic and Abdominal Surgery in Regional (Spinal, Peridural) Anesthesia, the Utility of the Technique during COVID-19 Pandemic - Attila Louis Major; Kudrat Jumaniyazov; Shahnoza Yusupova; Ruslan Jabbarov; Olimjon Saidmamatov; Ivanna Mayboroda-Major (Medicines, 2021)
Background: laparoscopic surgery is mainly performed in general anesthesia. Symptomatic patients infected with COVID-19 needing surgery are however at higher risk for COVID-19 complications in general anesthesia than in regional anesthesia. Even so, Covid transfection is a hazard to medical personnel during the intubation procedure and treatment drugs may be in shortage during a pandemic. Recovery and hospital stay are also shorter after laparoscopy. Laparoscopy performed in regional anesthesia may have several advantages in limiting Covid. Methods: international literature on the risk of COVID-19 complications development was searched. 3 topics concerning laparoscopic surgery were reviewed: (1) Achievements in laparoscopy; (2) Advantages of regional anesthesia compared to general anesthesia; (3) Feasibility to perform laparoscopy in regional anesthesia in COVID-19 pandemic. The authors reviewed abstracts and full-text articles concerning laparoscopic surgery, gynecology, anesthesia and COVID-19. Studies published in PubMed, Embase, Cochrane Library and found in Google Scholar before 1st FEB, 2021 were retrieved and analyzed. Results: a total of 83 studies were found, all of them written in English. 17 studies could be found in gynecology and in general surgery about laparoscopy with regional anesthesia. In Covid time only one study compared laparoscopic surgery in general anesthesia to laparotomy and another study laparotomy in general anesthesia to regional anesthesia. Laparoscopy showed no disadvantage compared to laparotomy in Covid pandemic and in another study laparotomy in general anesthesia was associated with higher mortality and more pulmonary complications. Trendelenburg position can be a threat if used by inexperienced personnel and can induce unintended anesthesia of breathing organs. On the other hand Trendelenburg position has advantages for cardiovascular and pulmonary functions. Pneumoperitoneum of low CO2 pressure is well tolerated by patients. Conclusions: elective surgery should be postponed in symptomatic Covid patients. In inevitable emergency surgery intubation anesthesia in COVID-19 pandemic is as far as possible to be avoided. In COVID-19 pandemic, regional anesthesia is the preferred choice. The optimum may be the combination of laparoscopic surgery with regional anesthesia. Reducing the pneumoperitoneum is a good compromise for the comfort of patients and surgeons. A special case is gynecology, which needs to be performed in Trendelenburg position to free pelvic organs.